问题
解答题
分式化简: (1)
(2) (a-b+
(3)
(4)先化简,再求值:
|
答案
(1)原式=
- 10 (a-1)(a+4)
+ a+1 a-1 a-1 a-1
=
+ 10 (a-1)(a+4) a-1-(a+1) a-1
=
-10 (a-1)(a+4) 2 a-1
=
-10 (a-1)(a+4) 2(a+4) (a-1)(a+4)
=-2(a-1) (a-1)(a+4)
=-
;2 a+4
(2)原式=
•(a-b)2+4ab a-b
=(a+b)2-4ab a+b
•(a+b)2 a-b
=(a+b)(a-b)=a2-b2;(a-b)2 a+b
(3)原式=
÷3-x 2(x-2) (x+2)(x-2)-5 x-2
=
÷3-x 2(x-2) (x+3)(x-3) x-2
=
•3-x 2(x-2) x-2 (x+3)(x-3)
=-
;1 2x+6
(4)原式=
•a-b a+b
- (a+b)(a-b) a2+ b2
• a+b ab ab(a+b) a2+ b2
=
-(a-b)2 a2+ b2 (a+b)2 a2+ b2
=-4ab a2+ b2
又a2+b2+a-4b+
=0,故(a2+a+17 4
)+(b2-4b+4)=0即(a+ 1 4
) 2+(b-2)2=01 2
可得a=-
b=21 2
此时原式=
=-4×(-
)×2 1 2 (-
) 2+ 221 2
=4 17 4
.16 17